Risk factors from Framingham risk score for anthracyclines cardiotoxicity in breast cancer: A systematic review and meta-analysis - Jin, Hao; Xu, Jianfeng; Sui, Zheng; Wang, Lili (Frontiers in Cardiovascular Medicine, 2023)
Background Framingham risk score (FRS) is an effective tool for evaluating the 10-year risk of cardiovascular diseases. However, the sensitivity of FRS for anthracycline-induced cardiotoxicity is unclear. This meta-analysis aims to evaluate the correlation between risk factors (hypertension, hyperlipidemia, diabetes, smoking, and obesity) in FRS and anthracycline-induced cardiotoxicity in breast cancer. Methods We searched PubMed, EMBASE, and Cochrane Library for studies published from inception to January 2022 which reported cardiotoxicity due to anthracycline. Cardiotoxicity defined as any cardiac events were used as the primary endpoint. A total of 33 studies involving 55,708 breast cancer patients treated with anthracyclines were included in this meta-analysis. Results At least one risk factor was identified at baseline for the 55,708 breast cancer patients treated with anthracycline. Hypertension [I2 = 45%, Fixed, RR (95% CI) = 1.40 (1.22, 1.60), p < 0.00001], hyperlipidemia [I2 = 0%, Fixed, RR (95% CI): 1.35 (1.12, 1.62), p = 0.002], diabetes [I2 = 0%, Fixed, RR (95% CI): 1.29 (1.05, 1.57), p = 0.01], and obesity [I2 = 0%, Fixed, RR (95% CI): 1.32 (1.05, 1.67), p = 0.02] were associated with increased risks of cardiac events. In addition, smoking was also associated with reduced left ventricular ejection fraction (LVEF) during anthracycline chemotherapy [I2 = 0%, Fixed, OR (95% CI): 1.91 (1.24, 2.95), p = 0.003] in studies that recorded only the odds ratio (OR). Conclusion Hypertension, hyperlipidemia, diabetes, smoking, and obesity are associated with increased risks of anthracycline-induced cardiotoxicity. Therefore, corresponding measures should be used to manage cardiovascular risk factors in breast cancer during and after anthracycline treatment.